Crescimento, desenvolvimento e produção de espécies de fisális com mudas propagadas sob telas de sombreamento - Piva, André Luiz (2016)
The production of homogeneous orchards develops to the measure of quality. For a method of sexual propagation and more used. The present work had as objective to evaluate the growth of seedlings in growing environments. And, later, the establishment of seedlings, as well as the growth and production of plants under conditions of exposure to full sun. The study was conducted at the experimental station Antônio Carlos dos Santos Pessoa at the Unioeste campus of Marechal Cândido Rondon. The first experiment was conducted in a randomized complete block design in a subdivided plots scheme with 4 replicates. The treatments were constituted by environments protected with the screen White, Black, Green and Gray and full sun. As subplots were constituted of 3 species of cape gooseberry Physalis angulata, P. peruviana and P. pubescens. The second experiment was conducted in a block design to the case in a factorial scheme (5 x 3). The material used consisted of seedlings produced in the first experiment in the five environments and as three species of cape gooseberry, with 4 replicates. In the first experiment of the environments, it will exert a positive effect on the emergence of plants, an interaction between cultivation environments and species exerted on the emergence speed index, lap diameter, plant height, dry leaf biomass and the transpiration rate of seedlings. On the other hand, no effect was observed on net assimilation rate, photosynthetically active radiation, SPAD index, dry biomass of roots, stem and leaves, and no number of leaves per plant. As seedlings produced under black screen (sombrite), it is an emergency index and a higher rate of emergence independent of the species. In the second experiment, the environment of seedling production has no effect on the number of fruits per plant with full sun exposure. However, the effect was observed on the average number of leaves, diameter of the neck, number of flowers and dry mass of the shoot. The P. peruviana species had a lower number of leaves, flowers and fruits per plant than P. angulata and P. pubescens. The flowering / fruiting of the species. P. angulata was anticipated in relation to other species. The higher productivity presented by the species P. pubescens is due to the greater mass and diameter of the fruits